1965
DOI: 10.1084/jem.122.6.1173
|View full text |Cite
|
Sign up to set email alerts
|

The Immunological Development of the Human Fetus

Abstract: The immunogenesis of the human fetus has been investigated by means of the formation of immunoglobulins in vitro, immunofluorescence, morphological studies, and analysis of the immunoglobulins in the serum. Twenty fetuses which were born alive but died soon after delivery, were studied; their ages ranged from 13 to 31 weeks. The results of the spleen cultures demonstrated the synthesis of IgG and IgM, which starts at about the twentieth week of gestation. In the serum, IgM could be detected at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
46
0
1

Year Published

1970
1970
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(52 citation statements)
references
References 34 publications
5
46
0
1
Order By: Relevance
“…With respect to ontogeny of the IgA imune response, most early reports indicated that normal infants are born with less than 1 mg IgA/100 ml serum in their cord blood [13][14][15][16], and it was assumed that this IgA was of maternal origin. More recently, exploiting genetic techniques and 'experiments of nature', Mellander et al and Cedarqvist & Litwin were able to demonstrate that newborn infants are capable of synthesizing IgA [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to ontogeny of the IgA imune response, most early reports indicated that normal infants are born with less than 1 mg IgA/100 ml serum in their cord blood [13][14][15][16], and it was assumed that this IgA was of maternal origin. More recently, exploiting genetic techniques and 'experiments of nature', Mellander et al and Cedarqvist & Litwin were able to demonstrate that newborn infants are capable of synthesizing IgA [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…3 While both IgM and IgG plasma cells can usually be found by early second trimester, IgA-producing cells have not been observed before the 32nd week of pregnancy. 4 Serum IgA is usually undetectable at birth, and adult serum concentrations are not attained until around the time of puberty. In adults, the majority of human plasma cells produce IgA.…”
Section: Productionmentioning
confidence: 99%
“…Tlie onset of immunologic function in the developing human fetus has only recently heen studied systematically [11,12,16,32], ami existing data mainly concern imnninoglobulin synthesis. What is known about the onset of cellular immune function (delayed hypersensitivily) has been largely extrapolated from animal studies [15,23,32].…”
Section: Introductionmentioning
confidence: 99%